2012
DOI: 10.1007/s13320-012-0069-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of low coherence interferometry using broadband multi-Gaussian light sources

Abstract: Using a low coherence interferometry (LCI) model, a comparison of broadband single-Gaussian and multi-Gaussian light sources has been undertaken. For single-Gaussian sources, the axial resolution improves with the source bandwidth, confirming the coherence length relation that the resolution for single Gaussian sources improves with increasing spectral bandwidth. However, narrow bandwidth light sources result in interferograms with overlapping strata peaks and the loss of individual strata information. For mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
(42 reference statements)
1
15
0
Order By: Relevance
“…Table 2 lists distances through which the reflector was translated range from 50 µm to 860 µm. It is of interest to note that a setting of the reflector within the coherence gate of the source rather than at the exact ZPD produced the fringes as previously observed [3,4,5,7]. This quasi-aberrant measurement is often exhibited by readings of near ZPD e.g.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Table 2 lists distances through which the reflector was translated range from 50 µm to 860 µm. It is of interest to note that a setting of the reflector within the coherence gate of the source rather than at the exact ZPD produced the fringes as previously observed [3,4,5,7]. This quasi-aberrant measurement is often exhibited by readings of near ZPD e.g.…”
Section: Resultsmentioning
confidence: 66%
“…With quasi-monochromatic sources, the fringes are therefore visible through large path differences. However, where a broadband source illuminates the interferometer, fringes tend to wash out beyond the zero path difference (ZPD) point or the coherence gate of the light source [7,8]. This is the key feature that separates OCT sources from line sources such as Mercury lamps.…”
Section: Theory and Methodologymentioning
confidence: 99%
“…In this section, the time-domain OCT method, OCT light source characteristics, and SLD characteristics that are selected and briefly reviewed in previous research 7 and interferometrically investigated in this research, are reviewed more extensively.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…In previous research, 7 tandem Gaussian spectra were simulated, and it was observed that the A-scan resolution degraded with increasing spectral peaks and increasing spectral peak depths; that is, satellite peaks became larger and more numerous, degrading resolution. Though having exceptional bandwidth, many new sources for OCT present broad bandwidth spectra that are significantly non-Gaussian.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation